Factors that affect the English language teaching learning process in Ecuadorian public high schools. - Matovelle García, Patricia María (2013)
The purpose of this study is to analyze the factors that affect the English language teaching learning process in Ecuadorian public high sch.This research was carried out in Guayaquil, and it was focused on five public high schools settled in the north side of the city. The sample consisted of fifteen English teachers and fifteen students, who were applied a questionnaire especially designed for each. Besides, classroom observations of those groups have been done, addressing important issues. The aspects considered in this research were the factors concerning teachers, such as teaching proficiency, methods and techniques; factors concerning students, especially their needs, level, and learning styles; factors related to classrooms, like the space, and resources available for the different activities; and finally the factors that concern educational institutions, such as lesson planning and monitoring. After having a complete analysis and interpretation of the data for the proposed research, it was established the need for better spaces and resources for teaching English, which allow the learners motivation and progress, as well as the constant training and monitoring of teachers.